Display of multiple proteins on engineered canine parvovirus-like particles expressed in cultured silkworm cells and silkworm larvae - Xu, Jian; Sekiguchi, Tomofumi; Boonyakida, Jirayu; Kato, Tatsuya; Park, Enoch Y. (Frontiers in Bioengineering and Biotechnology, 2023)
Virus-like particles (VLPs) are promising adjuvant-free vaccine candidates to induce potent and specific immune responses to protect animals and humans from virus infections. Recent progress has been made dramatically in decorating VLP on the surface or inside with functional molecules, such as antigens or nucleic acids. However, it is still challenging to display multiple antigens on the surface of VLP to meet the requirement as a practical vaccine candidate. Herein this study, we focus on the expression and engineering of the capsid protein VP2 of canine parvovirus for VLP display in the silkworm-expression system. The chemistry of the SpyTag/SpyCatcher (SpT/SpC) and SnoopTag/SnoopCatcher (SnT/SnC) are efficient protein covalent ligation systems to modify VP2 genetically, where SpyTag/SnoopTag are inserted into the N-terminus or two distinct loop regions of VP2. The SpC-EGFP and SnC-mCherry are employed as model proteins to evaluate their binding and display. We showed that the VP2 variant with SpT inserted at the Loop 2 region significantly enhanced VLP display to 80% compared to 5.4% from N-terminal SpT-fused VP2-derived VLPs. The intact VLP formations of engineered chimeric VP2 variants and effective ligations orthogonally between those binding partners were confirmed by mixing purified proteins and co-infecting cultured silkworm cells or larvae with desired viruses. Our results indicate that a convenient VLP display platform was successfully developed for multiple antigen displays on demand. Further verifications can be performed to assess its capacity for inducing a desired immune response to pathogens.